A study on structural, compositional, microhardness and dielectric properties of LiInS2 crystal. (2nd January 2020) - Arunkumar, A.; Vijayakumar, P.; Magesh, M.; Ramasamy, P.; Rao, E. Nageswara; Rao, S. Venugopal
ABSTRACT: LiInS2 material was synthesized with high purity elements in homemade graphite crucible using horizontal furnace. LiInS2 single crystal was grown by Bridgman method with temperature gradient of 10–15°C cm −1 . The phase purity and cell parameters of grown LiInS2 crystal were confirmed by powder x-ray diffraction and single crystal x-ray diffraction respectively. The freezing point and enthalpy of melting were found to be 977°C and 26.26 Jg −1 respectively. The compositional analysis was made from inductively coupled plasma – optical emission spectrometry. Dielectric constant and dielectric loss was measured on (111) plane for various temperatures with frequency ranging from 50 Hz to 5 MHz. The hardness of the LiInS2 single crystal in the (111) plane was assessed for different loads. The laser damage threshold was evaluated for single shot and multiple shot at 532 nm. The photocurrents were measured for various temperatures with different filters.